2018
DOI: 10.1097/rlu.0000000000001890
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Case of Relapsing Polychondritis Detected by 18F-FDG PET/CT

Abstract: A 78-year-old man had fever, persistent wheezing, and serum C-reactive protein elevation. Malignant lymphoma was suspected because of mediastinal lymph nodes swelling on CT and soluble interleukin 2 receptor elevation. Symmetric F-FDG uptake in the tracheobronchial tree and bilateral auricles was observed on PET/CT. He was finally diagnosed as having relapsing polychondritis by auricular cartilage biopsy. F-FDG PET/CT may have crucial role in evaluating the extent of inflammation and deciding the biopsy site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Several studies have reported FDG uptake in diseases involving smaller arteries such as polyarteritis nodosa, 76 86 Wegener's granulomatosis, 87 Churg-Strauss syndrome, 88 or relapsing polychondritis. 89 90 91 Furthermore, FDG PET/CT may be able to differentiate between giant cell arteritis, Takayasu arteritis, and polyarteritis nodosa. 76 …”
Section: Aortitismentioning
confidence: 99%
“…Several studies have reported FDG uptake in diseases involving smaller arteries such as polyarteritis nodosa, 76 86 Wegener's granulomatosis, 87 Churg-Strauss syndrome, 88 or relapsing polychondritis. 89 90 91 Furthermore, FDG PET/CT may be able to differentiate between giant cell arteritis, Takayasu arteritis, and polyarteritis nodosa. 76 …”
Section: Aortitismentioning
confidence: 99%
“…However, the majority of RP patients with airway involvement were misdiagnosed at their rst visit with a median time of delay to diagnosis of up to more than 10 years [1,4,5] . Our early studies [6][7][8] , along with other previous case reports or sporadic cases have shown that 18F-uorodeoxyglucose positron emission tomography/computed tomography (F-18 FDG PET/CT, hereafter termed PET/CT) with its semiquantitative parameter SUV max may be a helpful tool in aiding in the diagnosis and for therapeutic response monitoring [9][10][11][12][13][14][15] , with typical imaging characteristics of FDG uptake in the laryngo-tracheo-bronchial tree, often symmetrically.…”
Section: Introductionmentioning
confidence: 99%